IMPLEMENTATION OF TEAMS GAMES TOURNAMENT (TGT) MODEL TO IMPROVE MOTIVATION IN LEARNING MATHEMATICS - Fitriastuti Fitriastuti; Siti Kamsiyati; Karsono Karsono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Motivation in learning is an important element in the learning activities. Motivation in learning mathematics of grade fifth student of State Primary School of Makamhaji 03 were still low. The purpose of the research is to improve motivation in learning mathematics in fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017-2018. This research form is Classroom Action Research and it was conducted in two cycles. Each cycle consists of four step, there are planning, acting, observing, and reflecting. The research subject is the fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017/2018 consists of 20 students. Technique of the data collecting  used  interview, observation, questionnaire, and documentation. Data validity were construct validity, content  validity, and triangulation of technique. Data  analysis  were  descriptive  comparative  statistics,  critical  analysis,  and  interactive analysis. Result of this research indicate that the motivation of learning  mathematics of grade fifth student of State Primary School of Makamhaji 03 from preaction until cycle II meeting 2 has increased to 90%. The conclusion of this research indicate that through Teams Games Tournament (TGT) model can improve motivation in learning mathematics in fifth grade students of State Primary School of Makamhaji 03 in the academic year 2017/2018.